1993
DOI: 10.1007/bf00399098
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening of connective tissue in elderly diabetic patients: relevance to diabetic nephropathy and oxidative stress

Abstract: Limited joint mobility seen in diabetes mellitus is thought to be the result of stiffening of periarticular connective tissue, which is presumably derived from increased cross-linking of collagen related to advanced glycation end products. In this study the extent of the stiffening of connective tissue was measured by the passive extension angle of the metacarpophalangeal joints in 205 elderly diabetic patients. Association with diabetic nephropathy, with which advanced glycation end products have recently bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In addition, no correlation was found between urinary 8-OHdG and the transversion mutational burden. However, oxidative stress is reported to be increased in people with diabetes mellitus or hyperglycaemia [3,4,5,6,7,8,9,10,11,12,13,14,15], suggesting that the somatic transversion mutational burden of mDNA is associated with oxidative stress derived from hyperglycaemia, which is not reflected by urinary 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no correlation was found between urinary 8-OHdG and the transversion mutational burden. However, oxidative stress is reported to be increased in people with diabetes mellitus or hyperglycaemia [3,4,5,6,7,8,9,10,11,12,13,14,15], suggesting that the somatic transversion mutational burden of mDNA is associated with oxidative stress derived from hyperglycaemia, which is not reflected by urinary 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of nephropathy in patients with LJM was reported as 40-90.9% in the literature and the relation with both micro and macroalbuminuria was shown [10]. In the study of Aoki et al [20] it was reported that nephropathy stage increased with the increasing severity of LJM.…”
Section: Discussionmentioning
confidence: 94%
“…Its more reactive open chain form only composes 0.002% of glucose molecules in vivo; therefore, significant collagen cross-linking requires a prolonged exposure to glucose. 23 A number of other AGE cross-links can also form, such as pentosidine, 24 DOGDIC (deoxyglucosone lysine-arginine cross-link), MOLD (methylglyoxal lysine dimer) and GOLD (glyoxal lysine dimer), 17,21 among others ( Figure 2). Deoxyglucosone and glyoxal are formed due to fragmentation of the Amadori product (an intermediate precursor product to an AGE in the Maillard reaction) and are highly reactive, although they are found in very small concentrations in vivo.…”
Section: Ahmed Et Almentioning
confidence: 99%